Parse tree visualization for Malay sentence (BMTutor) - Muhamad Noor, Yusnita; Jamaludin, Zulikha (Asian Research Publishing Network (ARPN), 2015)
In Malaysia, various efforts have been made by the government and language researchers in improving student’s ability of mastering Malay language (BM) due to their poor ability in grammar and sentence structure. In terms of technology, to date, there is no computer software or a prototype that is available that can help students in learning the BM sentence structure.Thus, BMTutor is introduced as a solution to this problem. BMTutor is a prototype for visualizing Malay sentence combined with sentence checker, sentence correction and word attribute components.BMTutor is intended to facilitate the learning process of sentence construction and grammatical structure in BM. It is also to enhance the learning process in BM that can be used by communities, especially students. An algorithm in designing BMTutor is discussed in this paper.The algorithm of the software is done sequentially as followed: 1) tokenizing 2) checking the number of words, 3) searching and comparing process to check the spelling or conjunctions, 4) assigning each word with a certain word class, 5) matching with rules, and 6) delivering/producing output (sentence correction or parse tree visualization, word attribute components, and parse tree from sentence examples).Based on the testing conducted, output from the development process shows that the prototype can correct all 15 invalid sentences and can produce parse tree visualization for all 20 sentences.